Rethinking democracy and education with Stanley Cavell - Paul Standish (FahrenHouse, 2013)
Stanley Cavell is a Harvard philosopher who, in writings spanning half a century has consistently returned to themes of education. Yet his writings are never programmatic, and he has never presumed to give advice to policy-makers or practitioners. He is interested in education as a critical dimension of human life. He shows how the autonomy of the individual is not to be separated from her role as a citizen. Understanding this requires attention to the criteria that sustain human practices and the development of judgement in relation to them. In philosophy and in ordinary life, this raises the question of scepticism, and Cavell's distinctive response to this, which links its manifestation in philosophy with literature and tragedy, and with aspects of ordinary human existence, is especially original. Cavell never writes in a technical way or in jargon, but his language makes significant demands on the reader, encouraging them to read with a new attentiveness: this itself is of pedagogical importance. The present discussion takes up these themes and relates them to crucial questions regarding the education of teachers. Received: 02/09/2013 / Accepted: 04/10/2013 How to reference this article Standish, P. (2013). Rethinking democracy and education with Stanley Cavell. Foro de Educación, 11(15), pp. 49-64. doi: http://dx.doi.org/10.14516/fde.2013.011.015.002